The resistive sensor a device for high-power microwave pulsed measurements. - Dagys, Mindaugas (IEEE Antennas & propagation magazine.)
In this paper we review a novel microwave power sensor, the operation of which is based on the electron-heating effect in semiconductors. The sensor has been specifically developed for the measurement of high-power microwave pulses. The sensor's principle of operation and its related circuitry are described. The influence of lattice heating on the sensor's performance is considered. The actual design and implementation of a waveguide-type sensor is presented, including details regarding its calibration. The application of the sensor for the measurement of microwave pulses at medium and high power levels is also presented.